2009
DOI: 10.1007/s11999-009-0730-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Outpatient versus Inpatient Total Knee Arthroplasty

Abstract: Level II, prognostic study. See Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
139
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(157 citation statements)
references
References 11 publications
13
139
0
Order By: Relevance
“…The recent changes in healthcare insurance and the aging US population make the appropriate exploration of outpatient procedures in terms of safety and cost-effectiveness more important than ever. The large number of recent orthopaedic studies comparing inpatient and outpatient procedures underscores this importance [2,5,9,10,15,16,24,25,29,30,37,40,48].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The recent changes in healthcare insurance and the aging US population make the appropriate exploration of outpatient procedures in terms of safety and cost-effectiveness more important than ever. The large number of recent orthopaedic studies comparing inpatient and outpatient procedures underscores this importance [2,5,9,10,15,16,24,25,29,30,37,40,48].…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of outpatient arthroplasty are reported to include higher patient satisfaction and reduced costs [15,29]. Multiple studies comparing the outcomes of inpatient with outpatient arthroplasty have been reported [2,5,9,10,15,16,24,25,29,30,37,40,48]. However, the difference between ''inpatient'' and ''outpatient'' is not as intuitive as one might think.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 Compared with hip arthroplasty, there is more data available with regard to the feasibility of performing total knee arthroplasty as an outpatient or 23-hour procedure. 7,17,[21][22][23][24][25] One randomized, doublemasked, placebo-controlled study showed that patients receiving 4 days of ambulatory femoral CPNB (n = 25) attained 3 critical discharge criteria (adequate analgesia, independence from intravenous analgesics, and independent ambulation >30 meters) in a median of 25 hours, compared with 71 hours for those receiving only an overnight ropivacaine infusion (n = 25, P<0.001). 25 A multicenter study using a nearly identical protocol reported that the extended ambulatory femoral infusion resulted in patients attaining the 3 discharge criteria in a median of 47 hours, compared with 62 hours for those of the control group (estimated ratio = 0.80, 95% CI: 0.66-1.00; P = 0.028).…”
Section: Knee Arthroplastymentioning
confidence: 99%
“…Such optimization is also known as 'outpatient joint arthroplasty' , a multimodal clinical pathway based on well-defined patient selection criteria [1][2][3] with the focus on discharge on the day of surgery while ensuring patients' safety [1,[4][5][6][7][8] and cost reduction [9,10,11]. Results have shown that quality of life after TKA, significantly improved within one year postoperative [11].…”
Section: Introductionmentioning
confidence: 99%